The KEPADATAN DAN POLA SEBARAN KERANG TAHU (Meretrix meretrix) SEBAGAI DASAR PENGELOLAAN SUMBERDAYA BERKELANJUTAN DI KAWASAN BATU BELUBANG KABUPATEN BANGKA TENGAH - Sari, Winda Amelia (Akuatik: Jurnal Sumberdaya Perairan, 2023)
Batu Belubang Village is one of the villages in Central Bangka Regency that has marine resources, one of which is tofu clams (Meretrix meretrix) which have economic and ecological potential and economic value. Tofu shells are animals that belong to the bivalve class that have a smooth and shiny shell, have a color and pattern on the outside surface of the shell. The purpose of the study was to determine the density, distribution pattern and relationship of tofu clam density with environmental parameters in the Batu Belubang Area. The study was conducted from May to June 2023 using survey methods and purposive sampling. The results of the study showed the highest density of tofu clams (Meretrix meretrix) in the Lower zone as much as 709.88 ind/ha and the lowest Middle zone as much as 570.99 ind/ha. The distribution pattern of tofu shells in the Upper zone obtained station 1 (0.17) with a clustering pattern, station 2 (-0.38), station 3 (-0.23) and station 4 (-0.33) uniform patterns. For middle zone station 1 (0.13) and station 3 (0.09) with a clustering pattern. While station 2 (-023) and station 4 (-0.33) pattern uniform. While the lower zone of station 1 (0.11) and station 2 (0.45) clustered patterns. For station 3 (-0.63) and station 4 (-0.23) the pattern is uniform. Based on the results of the Principal Component Analysis (PCA) test, salinity parameters that affect the density of tofu shells.